Male and female lecturers’ politeness strategies in EFL classroom - Novianti Arif; Iskandar; Andi Muliati; Andi Anto Patak (Center for Humanities and Innovation Studies, 2018)
This research identified types of politeness strategies used by a male and female lecturer in the EFL classroom based on the theory of Brown and Levinson. This research also investigated students’ perception toward the use of lecturers’ politeness strategies in the EFL classroom. This research applied the descriptive qualitative research design to describe the phenomena of politeness strategies. The subjects of this research were two English lecturers and fifteen university students. All of them chosen by using purposive sampling. The instrument of this research was observation and interview. The observation was conducted three meetings for every lecturer by using an audio recorder and field notes. The audio recorder was used to record lecturers’ utterances in the teaching and learning process. The field notes were used to obtain more accurate data. The interview was conducted to get the data from the students. The interview is done to find out about the students’ perception toward the use of politeness strategies in the classroom. The result of this research showed that male and female lecturers used four types of politeness strategies namely bald on-record, positive politeness, negative politeness, and off-record. Furthermore, the students perceived that male and female lecturer was polite. The students perceived that the male lecturer was more formal while the female lecturer was friendly.